Adoption of Sustainable Management Practices of Citrus Fruit Fly in Myagdi District, Nepal - Aryal, Bhawana; Thapa, Praseed; Shrestha, Lal Kumar; Basyal, Bikram; Pokhrel, Pandab; Poudel, Anisha (Journal of the Plant Protection Society, 2024)
Citrus fruit fly infestation poses a significant threat to citrus farming in Myagdi district, Nepal, affecting the productivity and sustainability of the crop. This study aimed to explore factors influencing the adoption of sustainable management practices for controlling this pest. Conducted across three municipalities, primary data were collected from 100 households through a pre-tested questionnaire and analyzed using STATA version 15. The binary logistic regression model revealed that extension support and household income were significant positive factors for adopting sustainable practices, while distance from the nearest market had a significant negative impact. Other factors, including age, gender, training, knowledge index, education, and organizational involvement, were not significant. These findings highlight the need to prioritize extension support, improve market access, and enhance household income in policies and programs promoting the adoption of sustainable management practices. For extension workers, this entails focusing outreach efforts on households located farther from markets and those with lower incomes, as these factors present significant barriers to adoption. This study provides insights for developing effective policies and strategies to address citrus fruit fly challenges.